x+3(x-3)=3

Simple and best practice solution for x+3(x-3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3(x-3)=3 equation:


Simplifying
x + 3(x + -3) = 3

Reorder the terms:
x + 3(-3 + x) = 3
x + (-3 * 3 + x * 3) = 3
x + (-9 + 3x) = 3

Reorder the terms:
-9 + x + 3x = 3

Combine like terms: x + 3x = 4x
-9 + 4x = 3

Solving
-9 + 4x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 4x = 3 + 9

Combine like terms: -9 + 9 = 0
0 + 4x = 3 + 9
4x = 3 + 9

Combine like terms: 3 + 9 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 4=-5y | | x^5+x^2=0 | | 2+(5/x)=7 | | 2-8(2d-1)=42 | | 6x+(x-0.5)=10 | | 6x-5=1x+4.25 | | -1/4x+2/3x+34 | | 180x=0.1 | | -2/3r=16 | | (-26)-(-24)= | | 3/4(4x-8)=x+8 | | 20d-2=5d+28 | | 8x-13y=1 | | 8/20c+4-5/20c=-9 | | (-15)-42= | | 4(3-y)=-y+8 | | 2[6u-1]-3u=9u+8 | | 16-4x^2+4xy-y^2= | | (2+4i)(2+4i)= | | -3y-7=2y+23 | | -2(b-4)=(-2b)+8 | | -3z-(-3/5+2)=-27/5-32 | | -3(x-3)+8(x-3)=6x+7-5x | | 10.7=d+43 | | 8+a+8+a=52 | | 23a=0 | | -16x^2-114x+14=0 | | 34+(-6)= | | -5x^2-30x=0 | | 4x(6-8x)+6=8 | | 14(2c+5)=-2c+9 | | 2-8(2d-1)=0 |

Equations solver categories